Industrial ecology and spaces of innovation - Green, Kenneth; Randles, Sally; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2006)
This book explores the disciplinary interfaces and practical implications of working across the two disciplines of industrial ecology (IE) and innovation studies (IS). Both disciplines have something to say about instigating environmental improvement and more sustainable futures. IE is predicated on the idea that social and economic systems mirror, or should be made to mirror, natural ecological systems. Proponents of IE devise models and techniques to trace material and energy resource flows as they move through social and economic systems. They propose policy and management improvements to increase the resource efficiency of such systems. By contrast, IS researchers work with the idea that innovation is a dynamic activity, vital to social and economic change and is shaped by a range of actors in industry, in government and in households.
pt. 1. Introduction -- pt. 2. Industrial ecology : techniques and cases -- pt. 3. Innovation systems : perspectives on transformation and variety -- pt. 4. Consumption and intermediation -- pt. 5. Governance and values -- pt. 5. Conclusion.
Includes bibliographical references and index.
Keywords: Industrial ecology; Electronic books